Experimental test of neutron intensity monitor with isomer production reaction for p-Li neutron source for boron neutron capture therapy - Tamaki, Shingo; Ohtani, Yuuki; Kusaka, Sachie; Sato, Fuminobu; Murata, Isao (Frontiers in Nuclear Engineering, 2024)
IntroductionBoron Neutron Capture Therapy (BNCT) is a promising cancer therapy. At present, development of accelerator based neutron source (ABNS) is underway to be utilized as a neutron source instead of nuclear reactor. However, it is known that the neutron field formed with accelerators have different characteristics depending on kinds of accelerators. We thus have to characterize the field before practical use.MethodIn the authors’ group, various neutronics characterization devices have been developed for our p-Li based BNCT machine named CSePT. In this paper, three neutron intensity monitor foils with an isomer production reaction for several tens to 800 keV of the p-Li neutrons were proposed, i.e., 107Ag, 115In and 189Os.Result and DiscussionFrom the experimental test results, two activation foils of 107Ag and 115In were confirmed to be a possible candidate as the monitor. However, the isomer production cross sections of them should be examined for practical use.